(untitled) (Bangladesh Journal of Medical Science, 2013)
Patients with acquired defects or congenital malformations of the palate exhibit disturbances in speech including hypernasality, nasal emission and decreased intelligibility of speech. Maxillofacial prosthesis is an art and science which not only replaces the lost structure but also sometimes restores the function.obturator is a prosthesis which closes the palate and pharyngeal defects and improving the speech and other function. This article presents a case report of a completely edentulous patient with palatal insufficiency rehabilitated prosthodontically with a hollow bulb obturator and a procedure for fabrication of closed hollow bulb obturator prosthesis. DOI: http://dx.doi.org/10.3329/bjms.v12i4.16665 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 435-438